Congruence relation in fuzzy partial hyperalgebras - Tahere Nozari; Elham Sadat Hoseini; Reza Ameri; Naimeh Onagh (Journal of Hyperstructures)
In this paper, we begin by introducing the concept of fuzzy partial hyperalgebra and exploring the relationships between congruence relations and strong congruence relations within this framework. We then construct an embedding of any fuzzy partial hyperalgebra into a fuzzy hyperalgebra, ensuring that all congruence relations on the embedded fuzzy partialhyperalgebra can be simultaneously extended to the corresponding fuzzy hyperalgebra.